Factors affecting the perceived readiness on the adoption of internal audit in public universities: evidence from Vietnam / Giang Nguyen Thuc Huong, Hanh Minh Thai, Dung Nguyen Thi Phuong and Dung Nguyen Tien - Huong, Giang Nguyen Thuc; Thai, Hanh Minh; Phuong, Dung Nguyen Thi; Tien, Dung Nyuyen (UiTM Press, 2023)
The study aimed to investigate the factors influencing the readiness of internal audit (IA) adoption in public universities based on the Theory of Planned Behavior (TPB). The study applied a mixed methodology. After surveying 120 leaders, lecturers, and department staff from 15 Vietnamese autonomous public universities to understand more about leaders' and experts' viewpoints on IA in universities, further qualitative research was conducted via the in-depth interview method. The results showed that the major influencing factors are self-efficacy, organizational support (including management commitment and facilitating conditions), perceived usefulness, and legal and social pressures. The paper contributes to the literature of IA pre-adoption by understanding the perceived readiness of IA in the public sector, especially in universities in an emerging market with unique characteristics. It also helps to enhance the understanding of the influencers on IA perceived readiness and provides helpful suggestions for accelerating IA implementation in emerging countries.